Authorship order and effects of changing bibliometrics practices. (January 2020) - Helgesson, Gert
Although the authorship order on published research plays a significant role for scientific merit in many research contexts, and therefore should be handled with great care not least for the sake of fairness, the practices of accrediting authorship positions vary greatly between different research areas. This paper makes the point, by help of a current example, that changes in bibliometrics practices may make an already disparate landscape even more confusing.